Efficiency and safety of subconjunctival injection of anti-VEGF agent – bevacizumab – in treating dry eye - Jiang X; Lv H; Qiu W; Liu Z; Li X; Wang W (Dove Medical Press, 2015)
Xiaodan Jiang,* Huibin Lv,* Weiqiang Qiu, Ziyuan Liu, Xuemin Li, Wei Wang Department of Ophthalmology, Peking University Third Hospital, Beijing, People’s Republic of China *These authors contributed equally as first authors Purpose: Dry eye is a chronic inflammatory ocular surface disease with high prevalence. The current therapies for dry eye remain to be unspecific and notcomprehensive. This study aims to explore safety and efficacy of a novel treatment – subconjunctival injection of bevacizumab – in dry eye patients.Methods: Sixty-four eyes of 32 dry eye patients received subconjunctival injection of 100 μL 25 mg/mL bevacizumab. Dry eye symptoms, signs (corrected visual acuity, intraocular pressure, conjunctival vascularity, corneal staining, tear break-up time, Marx line score, and blood pressure), and conjunctival impression cytology were evaluated 3 days before and 1 week, 1 month, and 3 months after injection.Results: Significant improvements were observed in dry eye symptoms, tear break-up time, and conjunctival vascularization area at all the visits after injection compared to the baseline (P<0.05). The density of the goblet cell increased significantly at 1 month and 3 months after injection (P<0.05). There was no visual and systemic threat observed in any patient.Conclusion: Subconjunctival injection of 100 µL 25 mg/mL bevacizumab is a safe and efficient treatment for ocular surface inflammation of dry eye disease. Keywords: anti-VEGF, bevacizumab, dry eye, ocular surface inflammation, subconjunctival